1993
DOI: 10.1007/bf00122195
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary report on a new composite material made of calcium phosphate, elastin peptides and collagens

Abstract: With a view to elaborating a bioactive bone substitute, the association of an artificial extracellular matrix, basically constituted of elastin-solubilized peptides (ESP) and type I + III collagens, with different types of calcium phosphates, was investigated. This paper describes the selective adsorption of ESP on some calcium phosphate samples, and the further association of the adsorbed peptides with type I + III collagens. A preliminary study of the material cytotoxicity was carried out, investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 10 publications
(5 reference statements)
1
21
0
1
Order By: Relevance
“…Such syntheses were denoted as ''biologically inspired'' which means they reproduce an ordered pattern and an environment very similar to natural ones [594][595][596]. The biologically inspired biocomposites of collagen and calcium orthophosphates (mainly, apatites) for bone substitute have a long history [29,364,499,[597][598][599][600][601][602][603][604][605][606][607][608][609][610][611][612][613][614][615] and started from the pioneering study by Mittelmeier and Nizard [616], who mixed calcium orthophosphate granules with a collagen web. Such combinations were found to be bioactive, osteoconductive, osteoinductive [29,585,[617][618][619] and, in general, artificial grafts manufactured from this type of the biocomposites are likely to behave similarly to bones and be of more use in surgery than those prepared from any other materials.…”
Section: Biocomposites With Collagenmentioning
confidence: 99%
“…Such syntheses were denoted as ''biologically inspired'' which means they reproduce an ordered pattern and an environment very similar to natural ones [594][595][596]. The biologically inspired biocomposites of collagen and calcium orthophosphates (mainly, apatites) for bone substitute have a long history [29,364,499,[597][598][599][600][601][602][603][604][605][606][607][608][609][610][611][612][613][614][615] and started from the pioneering study by Mittelmeier and Nizard [616], who mixed calcium orthophosphate granules with a collagen web. Such combinations were found to be bioactive, osteoconductive, osteoinductive [29,585,[617][618][619] and, in general, artificial grafts manufactured from this type of the biocomposites are likely to behave similarly to bones and be of more use in surgery than those prepared from any other materials.…”
Section: Biocomposites With Collagenmentioning
confidence: 99%
“…[104] Additionally, it has been reported that the osteoconductivity of hydroxyapatite can be further improved by associating a protein matrix with the mineral structure. [105] To mimic the unique structure of collagen and hydroxyapatite in natural bone, several kinds of hybrid biomaterials of collagen and hydroxyapatite have been developed. [101, 102, 105 -107] Because a reconstructed collagen matrix is mechanically too weak, maintaining its original shape is difficult when it is immersed in an aqueous solution, making the process of hybridization difficult to control.…”
Section: Hybridization Of Polymers and Inorganic Hydroxyapatitementioning
confidence: 99%
“…[705][706][707] Such syntheses were denoted as "biologically inspired" which means they reproduce an ordered pattern and an environment very similar to natural ones. [708][709][710] The biologically inspired biocomposites of collagen and calcium orthophosphates (mainly, apatites) for bone substitute have a long history, 33,442,597,[711][712][713][714][715][716][717][718][719][720][721][722][723][724][725][726][727][728][729][730] which began with the pioneering study by Mittelmeier and Nizard, 731 who mixed calcium orthophosphate granules with a collagen web. Such combinations were found to be bioactive, osteoconductive, osteoinductive, 33,699,732-734 and, in general, artificial grafts manufactured from this type of biocomposites are likely to behave similarly to bones and be of more use in surgery than those prepared from any other materials.…”
mentioning
confidence: 99%